Apontamentos sobre as emoções no contexto da educação integral de crianças pequenas - Guterres, Daniele Adriana Braz (Universidade do Vale do Rio dos Sinos, 2018)
This work has as its theme the emotions in the context of the integral education of small children in schools. For this, a bibliographical review was made, based on some theorists as Donald Winnicott, Henri Wallon and official documents that work with the issue of emotional development, integral education, affectivity in the learning process. I did an exploratory listening of some of my fellow educators who work in a private school in Porto Alegre. In order to understand what they think about socioemocinal development, affectivity and its relation to learning. Emotions have a strong influence on the learning process and their understanding in the educational context is very relevant because they are also a fundamental aspect in human development. The school needs to understand the need to treat the child beyond a mere receiver of knowledge, but to interact with affectivity so that it can build relationships of trust, thus contributing to the integral formation of the subjects.
Keywords: Emoções; Criança; Educação integral; Emotions; Child; Integral education